Penggunaan Chrysal untuk Memperpanjang Kesegaran Bunga Potong Mawar (Rosa hybrida L.) - PUTRA, DIMAS MANDALA; YUSWANTI, HESTIN; DARMAWATI, IDA AYU PUTRI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.5, No.4, Oktober 2016, 2016)
Chrysal Use to Extend Vaselife Cut Flowers (Rosa hybrida L.) Roses The demand for cut roses increasing but the problems that often occur in old rose cut flowers is the vaselife of flowers very short. One way that can be done to prolong the vaselife of flowers adaah by giving a solution of the marinade. The main function of a marinade solution is to maintain the vaselife of cut flowers as long as possible. Chrysal. Chrysal a marinade solution containing sucrose, dextrose and citric acid that can extend the life of flowers (vaselife) Another important factor in maintaining the vaselife of flowers is the availability of water. Water will go faster if the wider cross-section, for example by cutting the plant stem oblique. Objective To know the concentration of the shredded material Chrysal optimized to produce a maximum vaselife of flowers. Knowing the difference in the vaselife of roses stalks in pieces tilt and horizontal concentration Chrysal know the interaction between the treatment of cuts rose to the vaselife of roses. This research was conducted at the Laboratory of Post Harvest Technology Faculty of Agriculture, University of Udayana. This study uses a completely randomized factorial design with two factors. Based on this research, interaction between concentration Chrysal (L) by cutting the flower stalk (A) does not affect significantly (p ? 0.05) of all observed variables. In the single factor cutting flower stalk treatment (A) significant (p> 0.05) to variable interest weight loss, dantotal solution is absorbed, whereas the concentration of Chrysal (L) a very significant effect on the flowers begin to bloom, longer vaselife, and the total solution is absorbed.
Keywords: chrysal, cut flowers, vaselife, rosses